ANALYSIS OF GENDER DISCRIMINATION IN THE MOVIE TENGGELAMNYA KAPAL VAN DER WIJCK IN SOCIOLOGY PERSPECTIVE - Maulida Usna Aulia (Lembaga Sepercenter, 2026)
This research aims to analyze gender discrimination in the film